Efektivitas Metode Exponential Smoothing pada Penjualan Daging Ayam PT Ciomas Adisatwa Pemalang - Gunawan, Raadhi Muhammad; Baroh, Istis (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Chicken meat is one of the most commonly consumed sources of animal protein by the Indonesian people because it has good nutrition and is more affordable than other animal protein sources. Sales simulation in business activities is very important for companies to ensure adequate stock availability so that the company will not experience excess or shortage of stock and can maintain price stability. One of the methods that is often used is the Exponential Smoothing method. This study aims to analyze the difference from actual sales with the results of using the Exponential Smoothing method using alpha 0.1, 0.5, and 0.9, and to analyze the accuracy level of the use of the Exponential Smoothing method based on the MAPE method. This study uses a quantitative method. In this study, there is only 1 variable used, namely historical data on chicken sales at PT Ciomas Adisatwa Pemalang. The sample extraction technique used is the Purposiv sampling method. The conclusion of this study is that using a value of α= 0.5 is better than using other alpha values because the amount of difference between the simulation results and the actual sales data for November 2024 is only 26,242 KG, and for the accuracy of the Exponential Smoothing method using MAPE it is able to produce a value of only 15.683%, with this value the results of this forecasting simulation can be said to be good.